Gastrodia qingyunshanensis (Orchidaceae: Epidendroideae)—a new holomycotrophic orchid from Guangdong, China - Shi, Shi; Yang, Haijun; Wei, Xuefen; Liang, Qianyu; Yang, Xindong; Zeng, Xianxing; Xie, Chonglin; Chen, Liubao; Huang, Qinghua; Zeng, Guohong; Jiang, Zhurong; Xu, Han; et al. (Phytotaxa, 2021)
A new species of Gastrodia (Orchidaceae: Epidendroideae, Gastrodieae), G. qingyunshanensis, is described and illustrated from Guangdong, China. It is closely related to G. appendiculata C. S. Leou & N. J. Chung but can be distinguished by an urceolate (vs bell-like) and dark brown (vs pale greenish brown) perianth tube, the smaller petals (2.5 × 1.6 mm vs 4–5 × 5–6 mm), the shape of lip (oblong, 3×1.6mm vs ovate, 6–7×5mm), lack of elevated calli at the base of petal (vs having calli), and an appendage shorter than column (vs equal to column). The new species is only reported to occur on Qingyunshan Nature Reserve, Wengyuan County, China, and it is proposed to be Vulnerable (VU) according to the IUCN criteria.